Prognostic value of proliferation, PD-L1 and nuclear size in patients with superior sulcus tumours treated with chemoradiotherapy and surgery. Issue 2 (23rd July 2021) - Blaauwgeers, Hans; Lissenberg-Witte, Birgit I; Dickhoff, Chris; Duin, Sylvia; Thunnissen, Erik
Abstract : Aims: The aim of this study was to determine the relationship between proliferative activity, PD-L1 status and nuclear size changes after preoperative chemoradiotherapy (CRT) and the clinical outcome in patients with superior sulcus tumours. Methods: Proliferative activity (MIB-1) and PD-L1 status were estimated by immunohistochemistry in the tumour cells of resection specimen in a series of 33 patients with residual tumour after trimodality therapy for a sulcus superior tumour between 2005 and 2014. A morphometric analysis of both pretreatment and post-treatment tumour materials was also performed. Results were related to disease-free survival and overall survival. Results: Low proliferative activity (<20% MIB-1) was associated with better overall survival: 2-year overall survival of 73% compared with 43% and 25%, respectively, for moderate (MIB-1 20%–50%) and high (MIB-1 >50%) proliferative activity (p=0.016). A negative PD-L1 status (<1% positive tumour cells) was also associated with better overall survival (p=0.021). The mean nuclear size of normal lung tissue pneumocytes was significantly smaller compared with the mean nuclear size of tumour cells of the resection specimens (median difference −38.1; range −115.2 to 16.0; p<0.001). The mean nuclear size of tumour cells did not differ between pretreatment biopsies and resection specimens (median difference −4.6; range −75.2 to 86.7; p=0.14). Nuclear size was not associated with survival (p=0.82). Conclusions: Low proliferative activity determined by MIB-1 as well as a negative PD-L1 expression are significantly associated with better overall survival in patients with residual tumour after CRT for superior sulcus tumour.